American education - Spring, Joel (McGraw-Hill, 2002)
Clear, concise, and authoritative—compact and affordable, too—with scholarship that is often cited as a primary source, American Education brings up-to-date information and challenging perspectives to teacher educators’ classrooms. Revised every two years, American Education provides a fresh, concise, and up-to-date introduction to the historical, political, social, and legal foundations of education and to the profession of teaching in the United States. This edition introduces a new chapter reference guide to the No Child Left Behind Act, provides a fresh look at multiculturalism and multilingualism, and presents a new discussion of the link between schooling and the growing gap between rich and poor.